Janiceps Perosomus Elumbis: A Rare Fetal Monstrosity in Holstein Friesian Cattle - Gulia, N.; Bisla, A.; Honparkhe, M.; Singh, B. (The Indian Journal of Animal Reproduction, 2021)
The present clinical article reports a rare case of Janiceps Perosomus elumbis fetal  monster in a Holstein Friesian (HF) cross bred cattle and its successful per-vaginal  delivery using partial fetotomy. A HF crossbred cattle was presented with history  of completed gestation period with rupture of water bag 6 h ago and straining with  failure of delivery of fetus per-vaginum. The animal was examined at field level  and both forelimbs were pulled by the local paravet with retention of head inside  the birth canal. Per-vaginal examination revealed fetus in anterior longitudinal  presentation, dorso-sacral position with both forelimbs extended in birth canal  and two heads. The fetotomy was done for decapitation of both the heads. Then,  the fetus was delivered per vaginal by traction. The fetal monster was enumerated  as “Janiceps Perosomus elumbis” as the two heads were facing opposite to each  other with absence of vertebrae after thoracic region.
Keywords: Perosomus elumbis; Cattle; Dystocia; Janiceps; Monster